Public Health and Medical Preparedness for a Nuclear Detonation: The Nuclear Incident Medical Enterprise. Issue 2 (February 2015) - Coleman, C. Norman; Sullivan, Julie M.; Bader, Judith L.; Murrain-Hill, Paula; Koerner, John F.; Garrett, Andrew L.; Weinstock, David M.; Case, Cullen; Hrdina, Chad; Adams, Steven A.; Whitcomb, Robert C.; Graeden, Ellie; et al.
Abstract : Abstract: Resilience and the ability to mitigate the consequences of a nuclear incident are enhanced by (1) effective planning, preparation and training; (2) ongoing interaction, formal exercises, and evaluation among the sectors involved; (3) effective and timely response and communication; and (4) continuous improvements based on new science, technology, experience, and ideas. Public health and medical planning require a complex, multi-faceted systematic approach involving federal, state, local, tribal, and territorial governments; private sector organizations; academia; industry; international partners; and individual experts and volunteers. The approach developed by the U.S. Department of Health and Human Services Nuclear Incident Medical Enterprise (NIME) is the result of efforts from government and nongovernment experts. It is a "bottom-up" systematic approach built on the available and emerging science that considers physical infrastructure damage, the spectrum of injuries, a scarce resources setting, the need for decision making in the face of a rapidly evolving situation with limited information early on, timely communication, and the need for tools and just-in-time information for responders who will likely be unfamiliar with radiation medicine and uncertain and overwhelmed in the face of the large number of casualties and the presence of radioactivity. The components of NIME can be used to support planning for, response to, and recovery from the effects of a nuclear incident. Recognizing that it is a continuous work-in-progress, the current status of the public health and medical preparedness and response for a nuclear incident is provided.